[BP.08.04] COSYNTROPIN INFUSION SIGNIFICANTLY INFLUENCES THE RESULTS OF ADRENAL VENOUS SAMPLING IN PATIENTS WITH PRIMARY ALDOSTERONISM. (September 2017) - Solar, M.; Krajina, A.; Ballon, M.; Ceral, J.
Abstract : Objective: Adrenal venous sampling (AVS) in primary aldosteronism (PA) enables to identify the patients with unilateral form of the disease who can profit from adrenalectomy. Based on the available evidence, it is not clear whether to perform AVS procedure at rest under physiological conditions or following adrenal stimulation by adrenocorticotropin analogue consyntropin. Because of this reason, we performed a study to compare the diagnostic value of both AVS protocols. Design and method: The patients enrolled in the study underwent AVS both at rest and during adrenal stimulation by continuous infusion of cosyntropin. AVS procedure was considered successful provided cortisol concentrations in both adrenal samples were at least three times higher compared to peripheral blood at rest, and at least five times higher during adrenal stimulation. Cortisol corrected aldosterone concentration (AC) in adrenal samples was used to compare the aldosterone secretion between both adrenals. Lateralization index (LI) was calculated as a ratio of AC (dominant adrenal) to AC (non-dominant adrenal). Abnormal lateralization of aldosterone secretion was defined by LI >2 and >4 for AVS performed without and with adrenal stimulation. The results of both protocols were compared in respect to the procedural success and the diagnosis of the lateralization of the aldosterone secretion. Results: The study enrolled 46 patients who underwent 51 AVS. Procedural success without adrenal stimulation was observed in 32 (70%), and in 42 (91%) with adrenal stimulation. Both AVS protocols were successful in 31 (67%) individuals. In these patients, the lateralization of aldosterone secretion without adrenal stimulation was noted in 24 (77%), and in 14 (45%) when the AVS was performed during adrenal stimulation. Conclusions: Adrenal stimulation by cosyntropin infusion increases the success rate of the AVS procedure but may mask the lateralization of aldosterone secretion in some patients.